Música infantil y su impacto en el desarrollo socioemocional de niños de Educación Inicial II - Guasgua Tisalema, Katty Johanna (2025)
The project's theme is "Children's music and its impact on the socio-emotional development of children in Early Childhood Education II". Music is key in the comprehensive education of children, it is used to promote cognitive, emotional and social skills at an early age. The objective is to determine the impact of children's music on the socio-emotional development of children in Early Childhood Education II of the Aurora Estrada Ayala Educational Unit in Ramírez Pérez. The problem of the lack of resources and strategies that promote socio-emotional development limits the child to face their emotions and challenges in their daily and school activities; The methodology was mixed, descriptive, non-experimental, documentary and field design, the sample was 1 teacher and 25 students, the techniques were interview and observation. Results revealed that 56% of parents do not know the benefits of music in teaching, teachers are not up to date with new strategies, they consider music as an important tool, however, the lack of resources for its application is an obstacle, 52% of children cannot change their body expression according to the rhythm, 48% show distrust, shyness and anger, 44% do not recognize their emotions, are insecure, 72% are happy to work with music. Children's music helps assertive communication, regulate emotions, self-esteem and strengthens interpersonal relationships, its application is important to improve the development of children during their growth stage in a harmonious school environment for their emotional well-being.